Parapapillary gamma and delta zones in high myopiaA - Jonas, Jost B. (Retina, 2018)
Purpose: To examine parapapillary zones gamma and delta in highly myopic eyes. Methods: The retrospective observational study included patients attending the Tokyo high myopia clinics. Fundus photographs were morphometrically examined. Results: The study population included 600 eyes (304 individuals) with a mean age of 62.7 ± 14.3 years (range: 13-90 years) and mean axial length of 29.6 ± 2.2 mm (range: 23.2-35.4 mm). In multivariate analysis (regression coefficient r2:0.90), larger horizontal gamma zone diameter was correlated with wider delta zone diameter (P < 0.001; standardized regression coefficient beta: 0.81), higher ratio of vertical-to-horizontal disk diameter (P < 0.001; beta: 0.10), shorter fovea-outer gamma zone border distance (P < 0.001; beta: −0.19), longer disk-fovea distance (P < 0.001; beta: 0.18), and higher count of chorioretinal atrophic lesions (P < 0.001; beta: 0.07). Longer horizontal delta zone width was correlated with longer horizontal gamma zone diameter (P < 0.001; beta: 1.00), longer horizontal disk diameter (P < 0.001; beta: 0.15), shorter disk-fovea distance (P < 0.001; beta: −0.19), longer fovea-outer gamma zone border distance (P < 0.001; beta: 0.19), and smaller diameter of the largest chorioretinal lesion (P = 0.03; beta: −0.04). Longer width of both zones together was associated with longer horizontal disk diameter (P < 0.001; beta: 0.31), higher ratio of vertical-to-horizontal disk diameter (P = 0.001; beta: 0.18), longer disk-fovea distance (P < 0.001; beta: 0.19), shorter fovea-outer gamma zone border distance (P < 0.001; beta: −0.18), higher number of chorioretinal lesions (P < 0.001; beta: 0.30), and longer vertical distance between the superior and inferior temporal arterial arcade (P = 0.001; beta: 0.13). Conclusion: Larger gamma and delta zones were correlated with larger optic disk and more marked vertical optic disk rotation, longer disk-fovea distance, higher number of chorioretinal lesions, and longer temporal vascular arcade diameter. Parapapillary gamma and delta zones may develop before chorioretinal lesions develop and enlarge.
Gesehen am 07.09.2020